The Effects of UGC in Instagram Stories on Brand Perception and Purchase Intention: Analysis of UGC in small and large businesses - Costa, Julie (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence